High Incidence of Pathogenic Streptococcus agalactiae ST485 Strain in Pregnant/Puerperal Women and Isolation of Hyper-Virulent Human CC67 Strain - Li, Liping; Wang, Rui; Huang, Yan; Huang, Ting; Luo, Fuguang; Huang, Weiyi; Yang, Xiuying; Lei, Aiying; Chen, Ming; Gan, Xi (Frontiers in Microbiology, 2018)
Group B streptococcus (GBS) is the major pathogen causing diseases in neonates, pregnant/puerperal women, cows and fish. Recent studies have shown that GBS may be infectious across hosts and some fish GBS strain might originate from human. The purpose of this study is to investigate the genetic relationship of CC103 strains that recently emerged in cows and humans, and explore the pathogenicity of clinical GBS isolates from human to tilapia. Ninety-two pathogenic GBS isolates were identified from 19 patients with different diseases and their evolution and pathogenicity to tilapia were analyzed. The multilocus sequence typing revealed that clonal complex (CC) 103 strain was isolated from 21.74% (20/92) of patients and ST485 strain was from 14.13% (13/92) patients with multiple diseases including neonates. Genomic evolution analysis showed that both bovine and human CC103 strains alternately form independent evolutionary branches. Three CC67 isolates carried gbs2018-C gene and formed one evolutionary branch with ST61 and ST67 strains that specifically infect dairy cows. Studies of interspecies transmission to tilapia found that 21/92 (22.83%) isolates including all ST23 isolates were highly pathogenic to tilapia and demonstrated that streptococci could break through the blood-brain barrier into brain tissue. In conclusions, CC103 strains are highly prevalent among pathogenic GBS from humans and have evolved into the highly pathogenic ST485 strains specifically infecting humans. The CC67 strains isolated from cows are able to infect humans through evolutionary events of acquiring CC17-specific type C gbs2018 gene and others. Human-derived ST23 pathogenic GBS strains are highly pathogenic to tilapia.